MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN MATEMATIKA KELAS VII BUDI PEKERTI MELALUI PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) - Meliani Mansur; Dasa Ismaimuza; Muliati Muliati (Jurnal Elektronik Pendidikan Matematika Tadulako, 2025)
This research is classroom action research (PTK). The PTK model used is the Kemmis-Mc Taggart spiral model which aims to describe the improvement in student learning outcomes in class VII Budi Pekerti through the Teaching at The Right Level (TaRL) approach to integer material. This research was carried out with participants in this research totaling 36 students in class VII Budi Pekerti SMP Negeri 6 Palu, consisting of 20 male students and 16 female students. The data was analyzed descriptively and presented in graphical form. This research was taken based on 3 data on improving learning outcomes, namely starting from pre-cycle, cycle 1, and cycle 2 with a standard of completeness, namely N> 75. Obtained a percentage of completeness sequentially, Pre-cycle 22% with an average value of 50, cycle 1 55% with the average value is 70 and cycle 2 is 88% with an average value of 85. Based on the results of research that has been carried out on learning mathematics in integer material using the Teaching at the Right Level (TaRL) can improve student learning outcomes.